Answer :

We know a_{n} = a+(n-1)d

⇒ 6n – 7 = a+(n-1)d

⇒ 6n – 7 = a + nd – d

⇒ 6n – 7 = a – d + nd

Comparing the coefficients, we get,

6n = nd

d = 6

hence common difference is 6.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

There are n A.M.sRD Sharma - Mathematics

If x, y, z are inRD Sharma - Mathematics

Insert 7 A.M.s beRD Sharma - Mathematics

The 10^{th</su}RD Sharma - Mathematics

Insert five numbeRD Sharma - Mathematics

The 4^{th</sup}RD Sharma - Mathematics

Insert 4 A.M.s beRD Sharma - Mathematics

Show that x^{2}RD Sharma - Mathematics

An A.P. consists RD Sharma - Mathematics

How many terms arRS Aggarwal - Mathematics